Aspek radiografis dan biologis tulang dalam penilaian kualitas tulang pada osteoporosis - Yurika Ambar Lita; Azhari Azhari; Ria Noerianingsih Firman; Lusi Epsilawati; Farina Pramanik (Jurnal Radiologi Dentomaksilofasial Indonesia (JRDI), 2019)
Objectives: This scientific paper discusses aspects of biological bone and radiograph examination in helping diagnose systemic diseases with a decrease in bone quality more accurately. Literature Review: Osteoporosis often occurs in postmenopausal women because of reduced estrogen. Sign analysis is related to four important factors to assess bone quality, namely bone density, bone turnover, bone size and bone architecture. Mineral Bone Examination Density is a gold standard examination by the World Health Organization for the diagnosis of osteoporosis and bone biomarkers can provide an overview of the renovation process being carried out. Conclusion: Panoramic radiographs are expected to be a potential checkpoint for early detection of systemic diseases that manifest in the maxillofacial region with bone conversations characterized by bone enlargement, changes in bone microstructure and trabeculae that indicate changes in bone quality.